1997
DOI: 10.1017/s0022029997002379
|View full text |Cite
|
Sign up to set email alerts
|

Diarrhoeal toxin production at low temperature by selected strains of Bacillus cereus

Abstract: The growth of four Bacillus cereus strains producing diarrhoeal toxin at 32°C (F4433/73 and 29.155, isolated on the occasion of foodborne outbreaks, and F4581/76L and F4581/76R, two variants of a clinical strain), a weakly toxigenic strain isolated in routine analysis of food (3505M) and an emetic isolate (F3502/73) was investigated at low temperature. Biomass was determined by protein assay. Generation times were: for strain F3502/73, which grew at [ges ]12°C, 8·71 h (at 12°C); for other str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…In a first systematic approach we compared enterotoxin gene expression of a representative B. cereus strain set. Previous studies compared enterotoxin expression in single B. cereus strains under varying growth temperature (Van Netten et al, 1990 ; Fermanian et al, 1997 ; Rejasse et al, 2012 ), oxygen availability (Duport et al, 2004 ; Van Der Voort and Abee, 2009 ), lowered oxidation-reduction potential (ORP) (Duport et al, 2006 ; Zigha et al, 2007 ; Esbelin et al, 2009 ) and differing availability of nutrients, for instance sugars (Ouhib et al, 2006 ; Ouhib-Jacobs et al, 2009 ). In our study, quantification of nheB and hblD mRNA levels at early exponential and late exponential growth phase/transition phase by qRT-PCR revealed highly strain-dependent variations in toxin gene transcript levels and transcription efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…In a first systematic approach we compared enterotoxin gene expression of a representative B. cereus strain set. Previous studies compared enterotoxin expression in single B. cereus strains under varying growth temperature (Van Netten et al, 1990 ; Fermanian et al, 1997 ; Rejasse et al, 2012 ), oxygen availability (Duport et al, 2004 ; Van Der Voort and Abee, 2009 ), lowered oxidation-reduction potential (ORP) (Duport et al, 2006 ; Zigha et al, 2007 ; Esbelin et al, 2009 ) and differing availability of nutrients, for instance sugars (Ouhib et al, 2006 ; Ouhib-Jacobs et al, 2009 ). In our study, quantification of nheB and hblD mRNA levels at early exponential and late exponential growth phase/transition phase by qRT-PCR revealed highly strain-dependent variations in toxin gene transcript levels and transcription efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…In a study carried out by Kunisaki and Hyashi [27], they reported that resting cells of Escherichia coli formed N-nitrosamines at an optimum pH of 8.0, whereas an optimum pH of 3.4 was noticed during chemical nitrosation. Certain microbiological studies revealed that optimum growth of B cereus occurred at a pH range of 4.9 -10.0 [31,32]. However, Shukor et al [33] reported a pH range of 6.8 -7.0 for the optimum growth of this bacterium.…”
Section: Discussionmentioning
confidence: 99%
“…The diarrhoeal enterotoxins can be produced in the temperature range of 10-43°C, with an optimum of 32°C (Kramer and Gilbert 1989;Fermanian et al 1997). Production occurs between pH 5.5-10, with an optimum of pH 8 (Sutherland and Limond 1993).…”
Section: Virulence and Infectivitymentioning
confidence: 99%
“…Antimicrobials which inhibit the growth of B. cereus include benzoate, sorbates and ethylenediaminetetraacetic acid (Jenson and Moir 2003). Table 1: Limits for growth of B. cereus and toxin production when other conditions are near optimum (Kramer and Gilbert 1989;Sutherland and Limond 1993;ICMSF 1996;Fermanian et al 1997;Finlay et al 2000…”
mentioning
confidence: 99%